2023
DOI: 10.1111/vcp.13221
|View full text |Cite
|
Sign up to set email alerts
|

Needle tract seeding and malignant transformation of hepatocellular adenoma into well‐differentiated hepatocellular carcinoma in a dog

Oriol Jornet‐Rius,
Beatriz Agulla,
María Cristina López
et al.

Abstract: An 11-year-old neutered female golden retriever was referred with a history of a marked increase in liver enzyme activities. At presentation, complete blood count (CBC) and biochemistry panel showed a mild microcytic normochromic nonregenerative anemia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A recent study revealed that canine HCA transforms into HCC, which means recurrence may occur [56]. Therefore, this study demonstrated that Y RNA has a high potential for distinguishing canine HCA from HCC.…”
Section: Discussionmentioning
confidence: 60%
“…A recent study revealed that canine HCA transforms into HCC, which means recurrence may occur [56]. Therefore, this study demonstrated that Y RNA has a high potential for distinguishing canine HCA from HCC.…”
Section: Discussionmentioning
confidence: 60%